Comparison of the Antioxidant Activities of Organic Solvent Fractions of Leaf and Root Extracts of Peucedanum insolens Kitagawa - 오명석; 나란투야 난딘셋세그; 박찬주; 남길수; 조식제; 문자영 (한국생명과학회, 2023)
This study compared and analyzed the antioxidant activities of various organic solvent fractions from the leaves and roots of Peucedanum insolens Kitagawa. For this study, the dried leaves and roots of P. insolens Kitagawa were first extracted using 70% ethanol. The extracts were sequentially sub-fractionated in the order of hexane, chloroform, ethyl acetate, n-butanol, and water. The results revealed that the distribution of total phenolic contents by organic solvent fractions showed the same pattern in both the leaves and roots, with the highest in the ethyl acetate fraction (101.1±1.0 mg vs 71.2±3.4 mg of GAE/mg), but the lowest content in the hexane fraction (9.5±0.2 mg vs 7.5±2.1 mg of GAE/mg). The distribution of total flavonoid content in the organic solvent fractions showed the same pattern as that of total phenolic content. The results of DPPH, ABTS, and FRAP assays showed that the leaf and root extracts exhibited free radical scavenging activity in the same pattern, particularly, the ethyl acetate fraction had the highest activity. These results indicate that not only the roots of P. insolens Kitagawa but also the leaves possess potential substances that exhibit strong antioxidant activity. Significant correlations (R=0.903, p<0.0001, DPPH radical; R=0.891, p<0.001, ABTS radical; R=0.745, p<0.05, FRAP radical) between total phenolics and radical scavenging activities, but also significant correlations (R=0.867, p<0.001, DPPH vs. ABTS radicals; R=0.882, p<0.0001, DPPH vs. FRAP radicals; R=0.973, p<0.0001, ABTS vs. FRAP radicals) between radical scavenging activities were found in the organic solvent fractions. Therefore, as in the roots of P. insolens Kitagawa, the leaves possess strong antioxidant capacity and can be used as the main antioxidant material.